Stray tales of the Big Bend - Miles, Elton, 1917-1995 (Centennial series of the Association of Former Students, Texas A & M University ;, 1993)
"Centennial series of the Association of Former Students, Texas A & M University ; no. 46." A collection of tall tales and legends of the Big Bend Region of Texas.